Pengembangan Media Pembelajaran Matematika Berbasis Android Terhadap Kemampuan Berpikir Kritis Siswa Kelas IV SD - Zulfa Winanda; Masniladevi Masniladevi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
The purpose of this research is to develop an Android-based Mathematics learning media for training students' critical thinking skills. Therefore, researchers are interested in designing Mathematics learning media for Critical Thinking. This media development discusses the model proposed by Johannesson, P., and Perjons, E., (2014) using a five-step design research and development process, namely problem analysis, determining requirements, designing and developing products, demonstrating products, and developing products . Android-based learning media that are designed are validated by a validator and then tried out in class IV SDS Al-Azhar Bukittinggi to learn the practicality of the developed media. Based on the results of this study indicate that the Android-based Mathematics learning media for Critical Thinking that was developed was appropriate to be used in learning by teachers and students. Based on several stages of the trial, instructional media are categorized valid with a feasibility level of 68, and categorized as very practical with 90.7%. This research is expected to be a learning medium for Mathematics for Critical Thinking, and can be useful for teachers, students, and advanced researchers.